Cardiopulmonary effects of overnight indoor air filtration in healthy non-smoking adults: A double-blind randomized crossover study. (May 2018) - Cui, Xiaoxing; Li, Feng; Xiang, Jianbang; Fang, Lin; Chung, Ming Kei; Day, Drew B.; Mo, Jinhan; Weschler, Charles J.; Gong, Jicheng; He, Linchen; Zhu, Dong; Lu, Chengjian; et al.
Abstract: Background: More than 90% of the world's population lives in areas where outdoor air pollution levels exceed health-based limits. In these areas, individuals may use indoor air filtration, often on a sporadic basis, in their residences to reduce exposure to respirable particles (PM2.5 ). Whether this intervention can lead to improvements in health outcomes has not been evaluated. Methods: Seventy non-smoking healthy adults, aged 19 to 26 years, received both true and sham indoor air filtration in a double-blinded randomized crossover study. Each filtration session was approximately 13 h long. True and sham filtration sessions were separated by a two-week washout interval. The study was carried out in a suburb of Shanghai. Results: During the study period, outdoor PM2.5 concentrations ranged from 18.6 to 106.9 μg/m 3, which overlapped with levels measured in Western Europe and North America. Compared to sham filtration, true filtration on average decreased indoor PM2.5 concentration by 72.4% to 10.0 μg/m 3 and particle number concentration by 59.2% to 2316/cm 3 . For lung function measured immediately after the end of filtration, true filtration significantly lowered airway impedance at 5 Hz (Z5 ) by 7.1% [95% CI: 2.4%, 11.9%], airway resistance at 5 Hz (R5 ) by 7.4% [95% CI: 2.4%, 12.5%], and small airway resistance (R5 -R20 ) by 20.3% [95% CI: 0.1%, 40.5%], reflecting improved airway mechanics especially for the small airways. However, no significant improvements for spirometry indicators (FEV1, FVC) were observed. True filtration also significantly lowered von Willebrand factor (VWF) by 26.9% [95% CI: 7.3%, 46.4%] 24 h after the end of filtration, indicating reduced risk for thrombosis. Stratified analysis in male and female participants showed that true filtration significantly decreased pulse pressure by 3.3% [95% CI: 0.8%, 7.4%] in females, and significantly reduced VWF by 42.4% [95% CI: 17.4%, 67.4%] and interleukin-6 by 22.6% [95% CI: 0.4%, 44.9%] in males. Effect modification analyses indicated that filtration effects in male and female participants were not significantly different. Conclusion: A single overnight residential air filtration, capable of reducing indoor particle concentrations substantially, can lead to improved airway mechanics and reduced thrombosis risk. Highlights: Air filtration reduced indoor PM2·5 by 72.4% and particle number concentrations by 59.2%. An overnight filtration improved airway mechanics but not spirometric lung function. It also reduced levels of von Willebrand factor, an indicator of thrombosis risk. Impulse oscillometry provided sensitive measurements of airway mechanics.